Quality of life of patients with dementia in acute hospitals in Germany: a non-randomised, case–control study comparing a regular ward with a special care ward with dementia care concept - Daniel Lüdecke; Georg Poppele; Jens Klein; Christopher Kofahl (BMJ Open)
Objectives To identify factors that predict the quality of life (QoL) of patients with dementia in acute hospitals and to analyse if a special care concept can increase patients’ QoL.Design A non-randomised, case–control study including two internal medicine wards from hospitals in Hamburg, Germany.Setting and participants In all, 526 patients with dementia from two hospitals were included in the study (intervention: n=333; control: n=193). The inclusion criterion was an at least mild cognitive impairment or dementia. The intervention group was a hospital with a special care ward for internal medicine focusing on patients with dementia. The control group was from a hospital with a regular care ward without special dementia care concept.Outcome measures Our main outcome was the QoL (range 0–100) from patients with dementia in two different hospitals. A Bayesian multilevel analysis was conducted to identify predictors such as age, dementia, agitation, physical and chemical restraints, or functional limitations that affect QoL.Results QoL differs significantly between the control (40.7) and the intervention (51.2) group (p<0.001). Regression analysis suggests that physical restraint (estimated effect: −4.9), psychotropic drug use (−4.4) and agitation (−2.9) are negatively associated with QoL. After controlling for confounders, the positive effect of the special care concept remained (5.7).Conclusions A special care ward will improve the quality of care and has a positive impact on the QoL of patients with dementia. Health policies should consider the benefits of special care concepts and develop incentives for hospitals to improve the QoL and quality of care for these patients.